Measuring up to speech intelligibility. Issue 6 (10th October 2013) - Miller, Nick
Abstract: Improvement or maintenance of speech intelligibility is a central aim in a whole range of conditions in speech–language therapy, both developmental and acquired. Best clinical practice and pursuance of the evidence base for interventions would suggest measurement of intelligibility forms a vital role in clinical decision‐making and monitoring. However, what should be measured to gauge intelligibility and how this is achieved and relates to clinical planning continues to be a topic of debate. This review considers the strengths and weaknesses of selected clinical approaches to intelligibility assessment, stressing the importance of explanatory, diagnostic testing as both a more sensitive and a clinically informative method. The worth of this, and any approach, is predicated, though, on awareness and control of key design, elicitation, transcription and listening/listener variables to maximize validity and reliability of assessments. These are discussed. A distinction is drawn between signal‐dependent and ‐independent factors in intelligibility evaluation. Discussion broaches how these different perspectives might be reconciled to deliver comprehensive insights into intelligibility levels and their clinical/educational significance. The paper ends with a call for wider implementation of best practice around intelligibility assessment.